2014
DOI: 10.1136/bjophthalmol-2014-305159
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of posterior-approach ‘levatorpexy’ in congenital ptosis repair

Abstract: Posterior approach levatorpexy appears to be a safe and effective procedure for correction of congenital ptosis particularly with moderate or better levator function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
0
13
0
9
Order By: Relevance
“…Using the same success criteria, other studies of posterior approach ptosis surgery also reported similar success rate of over 80%. [5][6][7][8] McCulley et al 8,9 described a large series of traditional anterior approach to levator advancement and reported 77% success, and a simplified anterior approach technique of using a single adjustable suture had success rate of 74%. A study of 10 years' experience in MMCR in Asian unilateral ptosis reported 82.8% success defined by interlid MRD difference of r1 mm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the same success criteria, other studies of posterior approach ptosis surgery also reported similar success rate of over 80%. [5][6][7][8] McCulley et al 8,9 described a large series of traditional anterior approach to levator advancement and reported 77% success, and a simplified anterior approach technique of using a single adjustable suture had success rate of 74%. A study of 10 years' experience in MMCR in Asian unilateral ptosis reported 82.8% success defined by interlid MRD difference of r1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…27 Recent techniques of posterior approach ptosis repair were modified to prevent excising any conjunctival tissue. [4][5][6][7]24,27 Regarding to the open sky mullectomy, Peter et al 24 reported that 4% of eyelids developed complications related to postoperative surface drying and presence of sutures on the palpebral conjunctiva, including corneal abrasions, suture abscesses, prolonged postoperative pain, and blood cyst. We have not encountered any of these complications because our minimal incision technique does not require placing suture on the palpebral conjunctiva.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distinguishing difference between Collin's levator advancement and Malhotra's white line advancement is that the white line advancement technique simply advances the exposed posterior surface of the aponeurosis and does not breach the orbital septum nor includes a tarsectomy. The white line advancement technique has subsequently been modified into the levatorpexy procedure for congenital ptosis …”
Section: The Aponeurosis Vs Müller's Muscle In Ptosis Correctionmentioning
confidence: 99%